The Influence of Learning Motivation on Students’ Science Process Skills in Physics Learning From a Gender Perspective - Ramanda, Restu; Wijaya, Andika Kusuma; Rosdianto, Haris (Universitas Muhammadiyah Purworejo, 2026)
Physics learning emphasizes not only conceptual mastery but also the development of science process skills (SPS), which are essential for fostering critical, logical, and creative thinking. Previous studies have examined the influence of gender or motivation separately, but little attention has been given to their combined effect. This study aimed to investigate the influence of learning motivation and gender, both individually and interactively, on students’ SPS in physics learning. A quantitative survey with a comparative design was conducted involving 200 ninth-grade students (92 male and 110 female) at SMPN 4 Singkawang, selected using saturated sampling. Data were collected through a 22-item learning motivation questionnaire and a 10-item SPS test, and analyzed using two-way ANOVA after normality (Sig. = 0.200) and homogeneity (Sig. = 0.340) assumptions were met. The descriptive results showed a mean SPS score of 40.07 with a standard deviation of 13.47. The ANOVA results indicated that learning motivation (F = 1.866, Sig. = 0.137) and gender (F = 2.465, Sig. = 0.118) did not significantly affect SPS when considered separately. However, the interaction between motivation and gender was significant (F = 4.559, Sig. = 0.004), demonstrating that the combination of these variables influences students’ SPS outcomes. In conclusion, individual factors alone do not determine SPS, but their interplay shapes students’ scientific abilities. Therefore, instructional strategies in physics learning should integrate motivational and gender-responsive approaches to effectively enhance SPS.